The role of public relations in enhancing the quality of governmental service-a Field study in the Iraqi Airlines - الجادر سهير عادل; حسن علي عدنان (Journal of Economics and Administrative Sciences, 2016)
Abstract The research has discussed the public relations as dependent variable of its branch dimensions( confidence , commitment, control and satisfaction ) and the governmental service quality as independent variable of its branch dimensions (response, dependency, emphasis, tangibility and sympathy), and the research problem has represented by weakness of service quality presented to the customers dealing with company, which is observed via field co-existence of the researcher, where he observe that the quality presented in the company services, are inappropriate with the customers expectations level, also there is weakness of attention and recognition by the company for the concept of public relations in abroad way for its importance for the service organizations looking forward to expansion of its activities, where the sample was chosen of customers dealing with the Ministry of Transport-Iraqi airlines amounted(253), and the importance of the research sustained not from its intellectual frame, but extended to its applicable aspects in presented practical contribution concerned the way of finding the public relations in a form that enhance and support its service quality, where the researcher has strived to realize a collection of objectives, most important of them :-showing and detection the role played by the public relations in enhancing the service quality, and realizing these objectives, the researcher has depended on the analytical descriptive method, and he uses the questionnaire, personal interviews, field co-existence in the practice aspect of the research, also researches and studies related with the research subject in theoretical aspect with depending on (SPSS) to test and analyzing hypotheses of the relation and the impact among the research variables, and the most important statistic tools used in the analyzing are : the mean, standard deviation ,the coefficient variation and the simple linear liaison oefficient (spearman) to test the validly of liaison hypotheses and the simple linear regression to test the validly of effect, and the research to a collection of conclusions, most important the research implied the decrease of the company service quality level via which what are shown the tangible level, sympathy and safety, response, and reliability, and the researcher terminated the research with a collection of recommendation most important of them formulating strategy directing the company operations to focus on the customer means offering services according to the expectations and desires of the customers via performing questionnaire concerned the extent to which the company offering.